Implementation of landscape ecological knowledge in European urban practice. - (:unkn) unknown (My University, 2012)
Die Beiträge behandeln vielfältige Aspekte der Stadt- und Landschaftsökologie wie Ökosystem-Funktionen von Gründächern, die Anwendung des Konzept Ökostadt, die Umsetzung des Konzepts der Ökosystem-Dienstleistungen in Städten, die Wahrnehmung und Bewertung von Stadtgrün durch die Stadtbewohner, die Habitatvernetzung zur Verbesserung der urbanen Biodiversität, Planung von Grünnetzwerken und gute Beispiele zur Entwicklung einer urbanen grünen Infrastruktur.

This conference proceedings, which is based on the 2nd symposium of the European landscape ecologists in Laufen, focuses on urban landscapes and the implementation of landscape ecological knowledge in urban practice in cities and their surroundings. In twelve articles latest findings from landscape ecological research and praxis in urban areas are presented by scientists, planners and consultants from various countries in Europe and Japan. In front of the articles a preface by Prof. Dr. Jürgen Breuste (head of the RG Urban- and Landscape Ecology, University Salzburg) und Dr. Christoph Goppel (director of the Bavarian Academy for Nature Conservation and Landscape Management) is placed. After the preface follows the probably last manuscript, Systems Concepts for a Transdisciplinary Landscape Science (co-author: Prof. Ervin Laszlo) by Prof. Dr. Zev Naveh, who passed away in March 2011. Prof. Dr. Zev Naveh was an internationally acknowledged scientist and is hailed as one of the founding fathers and Nestor of today's landscape ecology. This conference proceedings is devoted to him.
Keywords: Landschaftspflege; Stadtökologie; Landschaftsökologie; Landschaftsbewertung